2003
DOI: 10.1021/tx0340302
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Microsomal Metabolic Activation of Hepatotoxic Clivorine in Rat

Abstract: The gender differences in the in vitro microsomal metabolic activation of hepatotoxic clivorine, a representative naturally occurring hepatotoxic otonecine type pyrrolizidine alkaloid, in Sprague-Dawley rats and their relation to the gender differences in susceptibility to clivorine intoxication were reported in the present study. Clivorine-induced liver damage in the male rat via metabolic activation to form the reactive pyrrolic ester followed by covalent binding to liver tissue constituents has been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
5
39
1
Order By: Relevance
“…Moreover, an additional pathway was found in female rats to directly metabolize clivorine, which might be responsible for detoxification to produce non/less toxic metabolite(s). However, identity of such a pathway, the formed metabolite, and enzyme(s) involved were not investigated in our previous study (Lin et al, 2003). In the present report, the microsomal metabolic pathways of clivorine in female rats, the generated metabolites, and the enzymes mediating these pathways are described.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, an additional pathway was found in female rats to directly metabolize clivorine, which might be responsible for detoxification to produce non/less toxic metabolite(s). However, identity of such a pathway, the formed metabolite, and enzyme(s) involved were not investigated in our previous study (Lin et al, 2003). In the present report, the microsomal metabolic pathways of clivorine in female rats, the generated metabolites, and the enzymes mediating these pathways are described.…”
mentioning
confidence: 71%
“…Compared with male rats, significantly lower metabolic activation rate to form toxic pyrrolic ester was observed in the hepatic microsomal metabolism in female rats, although the overall metabolic rates of clivorine in both sexes of rats were the same (Lin et al, 2003). Moreover, an additional pathway was found in female rats to directly metabolize clivorine, which might be responsible for detoxification to produce non/less toxic metabolite(s).…”
Section: Introductionmentioning
confidence: 81%
“…So far, it has been reported that some of the alkaloids led to potential gender-dependent toxicities due to their gender-related pharmacokinetics (25)(26)(27)(28)(29). Male SD rats were shown to be more susceptible to clivorine (a pyrrolizidine alkaloid) intoxications than female rats due to the gender-associated metabolism (26)(27)(28). Therefore, the characterization of veratramine pharmacokinetic profiles of both gender, particularly in gender-related metabolism and elimination, is considered essential for the evaluation of its safety and potential interactions with other drugs or herbs.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The species-, strain-or gender-depending variations in enzymatic activities or expressions, resulting in different overall balances of the detoxification and activation pathways, can influence the higher susceptibility of certain animals (e.g. male rat > guinea pig) to PA toxicity (Huan et al, 1998a;Lin et al, 2002Lin et al, , 2003Chung and Buhler, 2004;Lin et al, 2007).…”
Section: Metabolismmentioning
confidence: 99%